2013
DOI: 10.1021/jf305003h
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Lysimeter Experiment To Investigate the Leaching of Perfluoroalkyl Substances (PFASs) and the Carry-over from Soil to Plants: Results of a Pilot Study

Abstract: To study the behavior of perfluoroalkyl substances (PFASs) in soil and the carry-over from soil to plants, technical mixtures of perfluorooctanoic acid (PFOA) and perfluorooctane sulfonate (PFOS) at a concentration of 25 mg/kg soil were applied to 1.5 m(3) monolithic soil columns of a lysimeter. Growth samples and percolated water were analyzed for PFASs throughout a period of 5 years. In addition to PFOA/PFOS plant compartments and leachate were found to be contaminated with short-chain PFASs. Calculation sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 27 publications
6
56
0
Order By: Relevance
“…One recent study showed that about 0.001% of PFOA and 0.004% of PFOS accumulated in plants from soil (Stahl et al, 2013). Additionally, the presence of these compounds in remote locations suggests long-range transport of volatile precursors of PFASs, making volatilization one possible route of loss from soil (Prevedouros et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…One recent study showed that about 0.001% of PFOA and 0.004% of PFOS accumulated in plants from soil (Stahl et al, 2013). Additionally, the presence of these compounds in remote locations suggests long-range transport of volatile precursors of PFASs, making volatilization one possible route of loss from soil (Prevedouros et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The contribution to the intake from fruit, cereals, legumes, leafy and root vegetables (24 ng kg À1 bw d À1 , see S1) have been accounted for according to the uptake factors of PFOS from soil to the edible parts (0.003 reported for corn ear, 0.1 for oat grains, 0.01 for potatoes, and 0.05 for carrots, Yoo et al, 2011;Stahl et al, 2013). Under the conservative approach of a 0.05 uptake factor extended also to fruit, the contribution of all food of vegetable origin to the overall intake represents roughly 10% of the contribution given from food of animal origin under the modeled conditions.…”
Section: Discussionmentioning
confidence: 99%
“…According to Sepulvado et al (2011) it was then possible to model the occurrence of PFOS on agriculture soils and pasture as consequence of the regular land application of municipal biosolid, through the equation: y = 0.896x + 0.423. The transfer factor from contaminated soil to forages was derived from Yoo et al (2011) for hay from grass (Â0.25, as average for PFOS and PFOA and from Stahl et al (2013) for mais silage (Â0.17), on dry matter basis (Table 2). Therefore, for dairy and beef animals, it was possible to estimate the PFOS intake, expressed as ng kg À1 -body weight (bw) d À1 , accounting for the default animal nutrition and production parameters reported in Table 1.…”
Section: 2mentioning
confidence: 99%
“…Moreover, greenhouse pot experiments and artificially polluted soils do not present the actual behavior of weathered PFAAs in field soils. Stahl et al (2013) described a long-term lysimeter experiment that demonstrated the carry-over of PFAAs from spiked soil to plant under field conditions. Evidence for accumulation of PFAA congeners and fluorotelomer alcohols in the above-ground part of grasses grown in sludge contaminated soils was provided by Yoo et al (2011).…”
Section: Introductionmentioning
confidence: 99%